Graduate Social Workers’ Perceptions of Fieldwork Training: Some Reflections from India and Bangladesh - Dey, Joyashri; Dutta, Rajdeep (International Journal of Psychosocial Rehabilitation, 2020)
In social work education, fieldwork is a systematically planned ingredient for students. Fieldwork enriches students to experiment with theories, methods, and knowledgeto gather experiences in realistic situations. Nevertheless, the entire processes (from placement to evaluation) of field training come across various challenges before students. This qualitative study attempts to discuss the reflections of fifty graduate social workers’ perceptions of fieldwork training, supervision, and evaluation at their bachelor level of social work programs. It clarifies the prevailing discontent amid students on fieldwork. Finally, it provides suggestive measures that may add value to strengthen fieldwork training.